2002
DOI: 10.1111/j.1747-6593.2002.tb00412.x
|View full text |Cite
|
Sign up to set email alerts
|

The Hydro‐Ecology of Limestone Springs in the Wye Valley, Derbyshire

Abstract: Springs are unique freshwater habitats and represent ideal sites in which to examine the relationship between environmental variables and macro‐invertebrate communities. The results of three case studies infer that species assemblages are determined by the physical habitat conditions within a spring and the ecological requirements of the component species. The composition of the macro‐invertebrate community changes significantly along the longitudinal gradient of a spring‐brook, as predicted by ecological theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…However, Smith (2002) suggested that the capture of springs for bottled water operations is a significant threat, worldwide, to their integrity and persistence. Spring water quality largely depends on the underlying geology and the land uses of the recharge basin (van der Kamp 1995).…”
Section: Anthropogenic Threats To Springsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Smith (2002) suggested that the capture of springs for bottled water operations is a significant threat, worldwide, to their integrity and persistence. Spring water quality largely depends on the underlying geology and the land uses of the recharge basin (van der Kamp 1995).…”
Section: Anthropogenic Threats To Springsmentioning
confidence: 99%
“…The range of threats has been summarised by a number of authors (e.g. Smith 2002). Water permanence is a key factor influencing the number of crenobiontic species, endemism and biodiversity in spring habitats erman & erman 1995).…”
Section: Anthropogenic Threats To Springsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, few studies have compared benthic communities in springs (eucrenon) with those in springbrooks (hypocrenon) (McCabe & Sykora 2000;Smith 2002;Barquin & Death 2004. The above studies were conducted along a distance of up to 1 km downstream from the spring under various climatic conditions, whereas Resh (1983) and Von Fumetti et al (2007) on the physical changes along the course of springbrooks and on the responses of benthic macroinvertebrate communities to these changes were gathered by Mc Cabe (1998).…”
Section: Introductionmentioning
confidence: 99%
“…Especially for the structural separation into fine and coarse mineral substrates and particularly specific organic substrates such as CPOM and emergent macrophytes a faunistic relevance is detectable. Even in studies of karst springs in the Wye catchment in the Peak District National Park (Derbyshire) in England no dominant relationship between the occurrence of different microhabitats and the species composition of invertebrates was found [47][48]. The results obtained from the springs and springbrooks examined that discharge variability has a greater influence on macroinvertebrate community composition than the distribution and diversity of substrate types.…”
Section: Mineralmentioning
confidence: 80%